Histopathological Findings of 100 cases of Abnormal Uterine Bleeding and their Correlation with FIGO Classification - Nahar, Kamrun; Apsara, Suraiya; Hoque, Luna Farhana; Baby, Hosne Ara (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Abnormal uterine bleeding(AUB) is one of the most common gynaecological problems encountered in clinical practice. The PALM-COEIN classification for causes of AUB was proposed by the International Federation of Gynaecology and Obstetrics (FIGO) in 2011, which has gradually been applied in Bangladesh for the diagnosis of AUB. Objective: the objective of this study was to evaluate the prevalence of chronic AUB according to FIGO classification in reproductive age women , carry out histopathological study and analyze it,s clinicopathological pattern. Material and methods: this descriptive cross sectional study was carried out among 100 women of reproductive age (20-49 years) who presented with abnormal uterine bleeding (AUB) in the department of obstetrics and gynaecology of Dhaka Medical College Hospital during the period of January 2012 to December 2012. Clinical diagnosis was made according to PALM-COEIN classification on the basis of history, examination and necessary investigations. Endometrial sample and hysterectomy specimen were assessed by histopathology. Result: Thirty five (35%) percent patients were 41-45 years. Ninety two (92%) patients were married ,2(2%) were unmarried and 6(6%) were widow. Among married women 98% were fertile and 2% were subfertile. Most common presenting symptom was menorrhagia (48%), followed by metrorrhagia (25%) and polymenorrhoea was observed in 22% cases. Ovulatory dysfunction (AUB-O) was the most common cause of abnormal uterine bleeding among the non structural causes and it was 44% . AUB-L were the most common (30%) among the structural causes, followed by AUB-A(10%) and AUB-P(5%). Regarding histopathological findings most of the patients( 34%) revealed unremarkable histopathological findings. Other findings were leiomyoma 27(27%), adenomyosis 13(13%) and fibroid uterus with adenomyosis in 5(5%) cases. Conclusion: AUB –O was the leading cause of abnormal uterine bleeding and histopathological evaluation correlated well with the clinical diagnosis. Bangladesh J Obstet Gynaecol, 2019; Vol. 34(1): 22-27